Land speculation in Tokyo : a system dynamics model - Hashimoto, Masayuki; Saeed, Khalid; Amin, A.T.M. Nurul; Mori, Hiroshi; Government of Japan (Bangkok : Asian Institute of Technology, 1991)
The purpose of this study is, by using the System Dynamics method, to analyze the current urban land use in Tokyo and to search the effective policies to improve it. As the features of the current urban land use, Tokyo is suffering from the chronic shortage of land which became a cause to bring about the land boom in 1980s. Because of the strength of the System Dynamics method that it can dynamically analyze the effects of policies to the behavior of a city as a unified system, this method is applied to address the problem. Focusing on the behavior of the land price in commercial and housing districts, this study develops the model. As for speculation, this study assumes three types of speculation which are speculation on the basis of the fundamental value of land, the behavior of the price, and the expectation of other speculators' expectation. In conclusion, if speculation has significant influence on the current urban land use in Tokyo, firstly, the current social systems which cause the inefficiency of land use should be reformed. Secondly, the rate of the property tax should be raised. Thirdly, the supply of land should be increased by Improving the infrastructures. Lastly, the rate of the transaction tax should be raised.
A thesis study submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Land use -- Japan -- Tokyo